Role of magnetic-resonance imaging of fetus in diagnostics of congenital defects - A. M. Korostyshevskaya; A. A. Savelov (Бюллетень сибирской медицины, 2012)
Retrospective analysis of 78 MR images of fetus has shown 30% of coincidence of MR-imaging and ultrasonographic diagnoses, 37% of different diagnoses, and 33% — adjustments of ultrasonographic diagnosis and obtaining of additional information with MR imaging in 63% cases. The results obtained demonstrate clearly that MR imaging should be included in the algorithm of pregnancy follow-up, if some signs are revealed by ultrasonography.